2021
DOI: 10.1002/adfm.202010532
|View full text |Cite
|
Sign up to set email alerts
|

Double‐Side Crystallization Tuning to Achieve over 1 µm Thick and Well‐Aligned Block‐Like Narrow‐Bandgap Perovskites for High‐Efficiency Near‐Infrared Photodetectors

Abstract: Solution‐processed narrow‐bandgap Sn–Pb perovskites have shown their potential in near‐infrared (NIR) photodetection as a promising alternative to traditional silicon and inorganic compounds. To achieve efficient NIR photodetection, high‐quality Sn–Pb perovskite thick films with well‐packed, smooth, and pinhole/void‐free features are highly desirable for boosting the spectral absorption. Understanding the crystallization kinetics and tuning the crystallization are fundamentally important to reach such high‐qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 62 publications
1
30
0
Order By: Relevance
“…[ 24,69,71,119,120] Carrier lifetime ≈1-10 µs Time-resolved photoluminescence Time-resolved microwave conductance…”
Section: Remarkable Carrier Transport Propertiesmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 24,69,71,119,120] Carrier lifetime ≈1-10 µs Time-resolved photoluminescence Time-resolved microwave conductance…”
Section: Remarkable Carrier Transport Propertiesmentioning
confidence: 99%
“…Wallace C. H. Choy and co-workers have devoted extensive works in the crystallization kinetics of SnPb mixed perovskites and developing their efficient NIR photodiodes and imaging arrays. [24,25,218] They introduced Rb cations to MA Sn-rich SnPb mixed perovskites (the Sn content is 65%) to control crystallization for growing high-quality films. [25] Interestingly, incorporated Rb can effectively modify surface-energy-induced kinetic process.…”
Section: Wwwadvopticalmatdementioning
confidence: 99%
See 2 more Smart Citations
“…Perovskite materials, owing to their high carrier mobility, effective charge collection, efficient light absorption, and low-cost preparation by the solution method, are widely used as active layer materials in solar cells and photodetectors. , It was reported that the absorption range of perovskite materials can be effectively adjusted by changing the composition ratio of Cl – , Br – , and I – anions, which makes it possible to prepare a series of visible-blind spectrum tunable NIR photodetectors based on perovskite or perovskite/organic hybrid active layers. Lan et al reported the structure of CH 3 NH 3 PbI 3 (1700 nm)/PTB7-Th:PC 71 BM (200 nm) to accomplish an NIR narrowband perovskite-organic hybrid PDs with the CCN strategy.…”
Section: Introductionmentioning
confidence: 99%